Dilemmas of Central Banks in the Face of Quantitative Easing Policy - Pyka, Irena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The study focuses on the analysis of the character and form of quantitative easing policy, used by central banks during the global financial crisis. Its main aim is to assess the consequences of this policy, which are analysed from the point of view of both theory and practice. The study indicates their diversity, which determines the implementation of exit strategy by central banks.